CHARACTERISTIC AND THE DISTRIBUTTION OF SPASIO – TEMPORAL MACRONUTRIENT IN THE LAGOON AREA OF SEGARA ANAKAN - Rose Dewi; Muhammad Zainuri; Sutrisno Anggoro; Tjahjo Winanto; Hadi Endrawati (International Journal of Marine and Aquatic Resource Conservation and Co-existence, 2017)
ABSTRACTLagoon Area of Segara Anakan (SAL) have influence of natural and anthropogenic factors impacting on the increasing of macronutrient, ecologically SAL is downstream from several rivers watershed Citanduy. SAL is tropically moist and influenced monsoon wind, causing the fluctuated waters. The purpose of this research is to recognise the characteristic spatio-temporal makronutrien lagoon. The measurements of macronutrient, include: TN (Total of Nitrogen), NH3 (Ammonia), NO3- (Nitrate), TP (Total of Phosphate), and PO43- (Orthophospat), using methods of spectrophotometric and micro-kjeldahl. The spatial approach is done on 7 stations (S) with representations: (S) natural factors and (S) the presence of anthropogenic activities. The temporal approach (time series) for a year refers to the monsoon wind pattern (west, transition I, east and transition II) season. The results of laboratory tests are discussed descriptively and adapted to the Indonesian standart of waters quality. To facilitate spatio-temporal interpretation, the data is presented formingly a thematic map. Temporal results show in the west season, the highest macronutrient content is dominated by TN (0.587 ± 0.223) mg / L, NH3 (0.875 ± 1.290) mg / L and PO43- (0.390 ± 0.909) mg / L, while NO3- (0.185 ± 0.015 ) mg / L and TP (0.155 ± 0.026) mg / L highest during transitional season II. In the spatial approach, (S) with anthropogenic characteristics contribute to the whole height of the macronutrients. The effects of rainfall, anthropogenic pressure, aquatic hydrodynamics and the contribution of metabolic waste discharged from organisms, are thought to cause in the increasing of SAL macronutrients. Management and lagoon management strategies are required by the local government, stakeholders and communities to prevent the phenomenon of eutrophication of the lagoon. Key words: Macronutrient, Nitrogen, Phospate,  lagoon of  Segara Anakan